Entre a cruz e a espada: a reintegração de egressos do sistema prisional a partir da política pública do Estado - Lidiane de Almeida Barbalho (2012)
We have witnessed in our social structure, increased rates of imprisonment and, consequently, the number of prison system´egress. The social reintegration of these egresses is configured in the Criminal Sentencing Act as a role of the state and is a theme that finds practical challenges. There are policies currently betting on work and education as the means of egress living lawfully and honestly and stay away from violence and crime. Nationally, there has been, from the 1990s, the emergence of programs to support the prison system´egress. However, there are difficulties and limitations of the scope of these policies for egresses. They were created to enforce the law, having been drawn from the state. In Minas Gerais, the prison system´s egress has the intervention of the State Secretariat of Social Defense (SEDS) through the Social Reintegration Program Graduates of the prison system (Presp), created on 12/04/2003. In order to understand the impact of public policy in practical life of prison system´s egress´s life, we propose this research. The theoretical framework is the Ergology, which encompasses the concepts of "prescribed" - set of rules and standards - and "real" - what actually operates. Our study has the interest in uncovering the real, the concrete experience of social reintegration, the renormalization from what is prescribed by the Programme for Social Reintegration of prison system´s egress. To this end, we made a qualitative study using semi-structured interviews with workers from the program - professionals in the fields of Law, Psychology and Social Work, with prison system´s egress accompanied by Presp and management team. Data collection took place with proper interviews. However, helped to shape the field research participation in groups that occurred in the program, monitoring of individual assistance, observation of the work routine, informal conversations with employees and the public attended by the program, official publications and documents. A few years Psychology has launched his gaze in the formulation, implementation and execution of public and social policies, bringing out their dilemmas, conflicts and contradictions. We propose that research on public policy of reintegration of prison system´s egress of the State of Minas Gerais because we consider important to shed light on this issue and point out improvements in the social field, thus avoiding the recurrence of practices that harm the individual and their coexistence in society, taking into account the social conflicts and contradictions in which he is immersed. We note that in the field of prescription of the Programme, there´s the notion of support to the prison system´egress in the rescue of his citizenship after the deprivation of liberty. In the field of real, the egress of the prison system tends to follow the rules of honest world, within the law. What operates is an adaptation of the egress of the prison system to the new social life, not an exercise of their citizenship.